Television Story Angle and the Involvement on Learners with Intellectual Disability in Inclusive Education in Kenya - Lidubwi, Jackline; Bosire, Julius; Mutua, Joan (International Journal of Communication and Public Relation, 2023)
Purpose: The purpose of this paper was to examine the influence of television story angle and the involvement on learners with intellectual disability in inclusive education in Kenya. The paper was guided by the framing theory. Methodology: The study utilized the descriptive cross-sectional research design. A sample of 40 inclusive education schools, 16 Sub-County Education Officers, three television stations, 72 television programmes, three television producers and five key informants from the Kenya Association of the Intellectually Handicapped was drawn. Data was gathered through questionnaires, interview guides and code sheets. Quantitative data was analysed using descriptive and inferential statistics while thematic analysis was used to analyse qualitative data. Findings: The study established that while television stations have aired stories about inclusive education, the content aired seemed to portray people with disabilities as objects of pity, curiosity, evil, laughable, and burdensome. These qualities were repugnant to inclusion of learners with disabilities in education and were therefore counterproductive to inclusive education.